Astrocytes, HIV and the Glymphatic System: A Disease of Disrupted Waste Management? - Tice, Caitlin; McDevitt, Jane; Langford, Dianne (Frontiers in Cellular and Infection Microbiology, 2020)
The discovery of the glial-lymphatic or glymphatic fluid clearance pathway in the rodent brain led researchers to search for a parallel system in humans and to question the implications of this pathway in neurodegenerative diseases. Magnetic resonance imaging studies revealed that several features of the glymphatic system may be present in humans. In both rodents and humans, this pathway promotes the exchange of interstitial fluid (ISF) and cerebrospinal fluid (CSF) through the arterial perivascular spaces into the brain parenchyma. This process is facilitated by aquaporin-4 (AQP4) water channels located primarily on astrocytic end feet that abut cerebral endothelial cells of the blood brain barrier. Changes in expression or mislocalization of AQP4 from astrocytic end feet to the cell body results in decreased interstitial flow, thereby, promoting accumulation of extracellular waste products like hyperphosphorylated Tau (pTau). Accumulation of pTau is a neuropathological hallmark in Alzheimer’s disease (AD) and is accompanied by mislocalization of APQ4 from astrocyte end feet to the cell body. HIV infection shares many neuropathological characteristics with AD. Similar to AD, HIV infection of the CNS contributes to abnormal aging with altered AQP4, accumulation of pTau and chronic neuroinflammation. Up to 30% of people with HIV suffer from HIV‐associated neurocognitive disorders (HAND), and changes in AQP4 may be clinically important. In this review, we will provide an overview and discussion of the potential contributions of NeuroHIV on glymphatic system functions by focusing on astrocytes and AQP4, and discuss implications for these disruptions on NeuroHIV disease trajectory.